Transparent Omni‐Directional Stretchable Circuit Lines Made by a Junction‐Free Grid of Expandable Au Lines. Issue 31 (21st June 2021) - Kong, Minsik; You, Insang; Lee, Gilwoon; Park, Gyeongbae; Kim, Jaehyun; Park, Doowon; Jeong, Unyong
Abstract: Although various stretchable optoelectronic devices have been reported, omni‐directionally stretchable transparent circuit lines have been a great challenge. Cracks are engineered and fabricated to be highly conductive patterned metal circuit lines in which gold (Au) grids are embedded. Au is deposited selectively in the cracks to form a grid without any junction between the grid lines. Since each grid line is expandable under stretching, the circuit lines are stretchable in all the directions. This study shows that a thin coating of aluminum on the oxide surface enables precise control of the cracks (crack density, crack depth) in the oxide layer. High optical transparency and high stretchability can be achieved simultaneously by controlling the grid density in the circuit line. Light‐emitting diodes are integrated directly on the circuit lines and stable operation is demonstrated under 100% stretching. Abstract : A novel strategy to fabricate omni‐directional stretchable gold (Au) circuit lines with high transparency, high electrical conductivity, and negligible resistance change is presented. Metals are deposited directly over the crack‐controlled poly(dimethylsiloxane) surface forming grid inside the cracks. This study demonstrates a highly transparent, stretchable light‐emitting diode with a patterned Au line circuit board.